Deputy Minister of Higher Education visit to MLCC - Ahmad, Ibrahim (Pusat Bahasa Moden dan Sains Kemanusiaan, 2012)
6 November 2012 - The Honorable Dato’ Hou Kok Chung, the Deputy Minister of Higher Education Malaysia made a visit to MLCC and was also accompanied by Senator Dato’ Ng Fook Heng. They were given a cordial reception by Professor Dr Yuserrie Zainuddin, Assistant Vice Chancellor UMP (Student Affairs and Alumni); Professor Dr Abd. Jalil Borham, Dean of Centre for Modern Languages and Human Sciences; Chong Ah Kow, MLCC Coordinator; Abd Rahman Safie, Deputy Registrar; the volunteer teachers, Liu Xu, Yuan Jie, Zhang Cuicui and the committee members of the Inter-Varsity Mandarin Speaking Competition 2012. Dato’ Dr. Hou was impressed by the initiative taken by UMP to set up MLCC in collaboration with Hebei University. It was his first visit to MLCC and he took the opportunity to give a belated welcome to the three volunteer teachers from Hebei University.